A mobile health application use among diabetes mellitus patients: a systematic review and meta-analysis - Birhanu, Tesema Etefa; Guracho, Yonas Deressa; Asmare, Selamawit Worku; Olana, Diriba Dereje (Frontiers in Endocrinology, 2024)
Background Mobile health technologies are increasingly acknowledged as a cost-effective and convenient means of delivering top-notch healthcare services to patients in low- and middle-income countries. This research explores the utilization of mobile health applications in managing, monitoring, and self-care for adult diabetes mellitus (DM) patients. The objective is to gain insight into how diabetic patients currently utilize Mobile health applications for self-management and their inclination to use them in the future. Methods The authors conducted a systematic review and meta-analysis using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. They included articles that reported on the use of mobile/smartphone applications for diabetic mellitus disorders, focusing on ownership, application use, future interest in use, and use patterns. The search was conducted in the PubMed, Web of Science, Embase, and SCOPUS electronic databases, with various published articles from January 2016 up to February 2024. The methodological quality was evaluated using the Joanna Briggs Institute critical appraisal tool. Statistical techniques were applied, including the heterogeneity test, publication bias assessment, Egger’s test, and funnel plots. The pooled prevalence was calculated using meta-analysis proportion with a random-effects model. Results Thirteen studies were included, out of 4568 recognized articles. The pooled prevalence of mobile health application use for current diabetic management self-management, future interest in using the application for diabetic disorder self-management, and lack of belief in mobile health application users for self-management was 35%, 57%, and 39%, respectively. We observed significant heterogeneity (I2 = 97.7, p=<0.001), but no significant publication bias was detected on Egger’s test. Conclusions Our meta-analysis results show that over one-third of individuals use mobile health applications for diabetic self-management, and more than half of individuals would like to manage their diabetes mellitus in the future by using mobile health applications. These mobile health apps may be promising in future diabetes mellitus self-management. However, we still need to study the effectiveness of these apps. In addition, adopting mobile health apps based on the cultural context makes this self-management more achievable, practical, and impactful for individuals with diabetes. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier 42024537917.